PERBAIKAN KEKERASAN DAN STRUKTUR MIKRO LOGAM KUNINGAN SEBAGAI BAHAN PROPELLER DENGAN METODE SHOT PEENING - Yanti Pasmawati; Nugroho Tri Atmoko; Rizqi Ilmal Yaqin; Bambang Hari Priyambodo; Margono Margono (Jurnal Teknologi Terapan, 2023)
Brass metal is widely used as a supporting equipment material, one of which is a propeller. The propeller itself is one component of the boat that rotates and produces thrust energy. The continuous use of propellers results in degradation or a decrease in quality and service life. The degradation of the propeller is affected by the hardness, toughness, and corrosion resistance of the working environment. To improve the quality of the propeller, shot peening treatment was carried out on its surface. Shot peening is a continuous shooting process with fine particles in the form of steel balls on the surface of the object. Shot peening can increase the density of the microstructure and produce compressive residual stress which causes the surface hardness to also increase. Shot peening is carried out with variations in duration of 2, 4, 6, 8, and 10 minutes, 100 mm shooting range, and 7 Bar firing pressure. The steel ball particles used have a hardness of 40-50 HRC and a diameter of 5 mm. The results of the hardness test showed an increase in the surface hardness of the spesimens for a duration of 2, 4, 6, 8, and 10 minutes, respectively 189, 294, 302, 324, 330, dan 341 HV. The microstructure of the spesimen after shot peening looks tighter and denser. The highest hardness value is 341 HV or an increase of 80% compared to raw material.